Relevansi Kebijakan dalam Peningkatan Mutu Pendidikan Agama Islam - Asnawan Asnawan (Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni, 2020)
Policies on improving the quality of PAI education through the use of informationand communication technology in education in the form of developing systems,methods and learning materials using ICT. This activity will also develop a schoolinformation network system, infrastructure and human resources to support itsimplementation, both in the interests of education management and the learningprocess. By using ICT in the education of students in regular schools, residentslearn in non-formal education and students who need the development of localexcellence-based schools in each district of the city; the expansion of educationunits based on local excellence by regional governments is carried out in order tocarry out the mandate of Law Number 20 of 2003 concerning the NationalEducation System which will be gradually developed in each provinceand district/city